Attitude of Hungarian Young Adults Towards Bank Loans: The Risk Mitigation Trap - Béres, Dániel; Huzdik, Katalin (Public Finance Quarterly, 2022)
The aim of this study is to examine the attitude of young adults (18–25 years) towards bank loans. For the analysis we used two primary data sources (financial literacy surveys were executed in 2013 and 2020). The samples are non-representatives, the number of involved survey participants exceeded 1,740 in both cases. The survey included 6 sections with open and closed questions, as well as likertscales. It was found that the attitude of young adults towards the loans is negative. Between the 2013 and 2020 surveys the economic cycle showed prosperity. As a result, the respondents devalued the importance of the loans in the economy. Besides, the extreme rejection of having a bank loan was also mitigated. As for the bank loan experiences of the respondents it was found that the purposes of the borrowed loans are along the good criteria of financial literacy – the spendings examined can be considered as an investment for the future. Regarding the satisfaction level of the respondents with the bank loans the most important satisfactory factor was the expectations for the future. The measures taken after 2008 financial crisis such as re-defining consumer friendly lending and executing population supporting policy involving credit institutions resulted a mild positive effect on the attitude of the young adults towards bank loans. Risk avoidance results a trap situation that is against financial inclusion and results disequilibrium in demand and supply of banking services. The effect of the so called ‘risk mitigation trap’ can be reduced by developing the financial literacy.